Tunable optical delays based on Brillouin dynamic grating in optical fibers - Song, Kwang Yong; Lee, Kwanil; Lee, Sang Bae (OPTICAL SOC AMER, 2009)
We demonstrate a novel kind of tunable optical delays based on dynamic grating generated by Brillouin scattering in an optical fiber. An axial strain gradient is applied to a 15 m section of a polarization-maintaining fiber, and the Brillouin reflection grating is generated position-selectively by controlling the optical frequencies of Brillouin pump waves. Tunable time delays of up to 132 ns are achieved with an 82 ns Gaussian pulse. (c) 2009 Optical Society of America
Keywords: POLARIZATION-MAINTAINING FIBER; COHERENCE TOMOGRAPHY; SLOW LIGHT; SCATTERING; DISPERSION; AMPLIFIER